TINJAUAN YURIDIS NORMATIF TERHADAP PERALIHAN HAK ATAS TANAH KARENA PEWARISAN MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Anggoro, Denny Widi; Savitri, Miya Savitri (Jurnal Panorama Hukum, 2016)
The soil has a close relationship with humans for land has economic value for human life and can generate resources for the people. This is regulated in Article 33 paragraph (3) of the Act of 1945 which states: "The earth water and natural resources contained therein shall be controlled by the state and used for the greatest prosperity of the people." The problem in this research are: (1) What are the legal consequences of the transition of land rights for inheritance according to Government Regulation No. 24 of 1997 on Land Registration?; (2) What form of legal protection for the beneficiaries of transfer of rights on land for inheritance according to Government Regulation No. 24 of 1997 on Land Registry?. The research is normative juridical research (normative legal research). With the registration of a transfer of rights on land due to inheritance, the legal consequences arising for the heirs as holders of land rights are not guaranteed legal certainty. So it can be said that the heirs cannot take legal actions against the land title certificates.